Antinociceptive action of Vanillosmopsis arborea in male mice - Laura Inocencio Leite; Gerlânia de Oliveira Leite; Bruno Anderson Fernandes Silva; Severino Denício Gonçalves Sousa; Thales Coutinho; Renata Sampaio; Irwin Menezes; José Galberto Martins Costa; Adriana Campos (Mashhad University of Medical Sciences, 2017)
Objective: Vanillosmopsis arborea Baker (Asteraceae) has high economic value from Chapada to Araripe and its bark essential oil is a potential source of alpha-bisabolol. The present study aimed to elucidate the antinociceptive and antipruritic properties of the essential oil of V. arborea Baker (EOVA) in mice. Materials and Methods: The antinociceptive activity was assessed using the capsaicin, glutamate, hot plate and cold allodynia tests. The antipuritic effects were also verified based on histamine-induced scratching behavior. Results: EOVA reduced the paw licking induced by capsaicin, but not that induced by glutamate. The essential oil increased the latency time in the hot plate, attenuated the cold allodynia induced by acetone and inhibited histamine-induced scratching behavior. Conclusion: The experimental data demonstrated that EOVA showed central and peripheral antinociceptive activity and antipruritic effect.